Culpeper’s Impoliteness Strategies in the Devil May Cry 3 Cutscenes: Analyzing the 'Chaos’ Warm Welcome' Dialogues from Mission 13 - Yamjirin, Abdussalam Jabaruddin (DBSMB, Vocational College of Universitas Gadjah Mada, 2025)
This study focuses on analysing the impoliteness strategies used in “Devil May Cry 3: Dante’s Awakening” within Culpeper’s frameworks (1996, 2005, 2011), and Mission 13, Chaos’ Warm Welcome in particular. It forms a qualitative analysis of 48 identified instances of impolite utterances where the predominant strategy was found to be sarcastic/mock politeness (43.75%). This was followed by negative impoliteness (22.92%), bald on record (18.75%), positive impoliteness (12.5%), and withholding politeness (2.08%). The utterances serve the purpose of demeaning and provoking conflict and character idenitities, seen in Dante’s brutal counter to sharp challenges, paired with authoritarian aggression from Vergil, and Jester’s manipulative taunts. The excerpts illustrate how conflict in a power relation and emotional engagement within video game discourse is shaped by intended narrative framework through impoliteness. By using linguistic aggression, this study aims to fill a gap within pragma-interactive media by character portrayal and player involvement. It also demonstrates digital narrative frameworks show the need for deeper examination of structures by expressing how storytelling in a digital form employs elements of rudeness multifunctionally as a drivers of inner and outer conflict, character development, and immersion for the players. The findings highlight the loophole within interactive texts and the need to employ rudeness to build such texts.